Temporal Stability of Signal Quality in Non-Contact Biopotential Electrodes - Antonio Stanešić; Luka Klaić; Dino Cindrić; Mario Cifrek (Sensors)
Non-contact electrodes have garnered significant attention as an alternative non-invasive biopotential measurement method that offers advantages such as improved subject comfort and ease of integration into everyday environments. Despite these benefits, ensuring consistent signal quality over time remains a critical challenge, particularly in applications like electrocardiography (ECG), where accuracy and reliability are paramount. This study investigates the temporal stability of signal quality in non-contact biopotential electrodes, with a primary focus on ECG monitoring. Our measurements showed a significant change in the recorded signal quality during prolonged measurement periods, which impacts the integrity and reliability of the measurements. Furthermore, it significantly impacts any shorter (<10 min) consecutive measurements of influential parameters (such as properties of electrodes, dielectric, etc.) since it removes the crucial ceteris paribus principle: the signal may not change just due to the change in influential parameters, but also due to the passage of time. Through a series of controlled experiments, we analyze how factors such as temperature, pressure on the electrodes, and humidity influence signal quality over extended durations (10 min or more). The results demonstrate key insights into the temporal dynamics of non-contact electrode performance, identifying potential sources of signal degradation and avenues for mitigation.